Comparison of the Performance of Climbing Perch (Anabas testudineus Bloch) Filial 2 Fry and Natural Fry Treated in Acidic Swamp Waters, Jejangkit Village, South Kalimantan - Pahmi Ansyari; Slamat Slamat (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Ansyari F, Slamat S. 2020. Comparison of the performance of climbing perch (Anabas testudineus Bloch) filial 2 fry and natural fry treated in acidic swamp waters, Jejangkit Village, South Kalimantan. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 23-30.The aim of the study was to compare the performance (survival rate, growth and feed conversion) of climbing perch fish fry Filial 2 (F2) which has superior characteristics with natural fry that are culture in sour swamp waters. The study was carried out in swamp waters, Jejangkit Village, Barito Kuala Regency, South Kalimantan for 6 months (January to June 2019). This study compared fish performances generated from F2 fry of nature. Fishes were cultured in net (4 m x 2 m x 1 m) with the same stocking density of 100 fishes/m2 . The results showed that the survival rate of natural fry was 86.6% higher than that of F2 75.3%, but the relative growth of natural fry was 2,325% lower thanÂ F2 3,060% and feed conversion natural fry was 3.03 less efficient than F2 fry 2.62. It was concluded that the performance of F2 fry was better than natural fry, when maintained in acidic swamp waters.